2012
DOI: 10.1093/nar/gks873
|View full text |Cite
|
Sign up to set email alerts
|

An hnRNP-like RNA-binding protein affects alternative splicing by in vivo interaction with transcripts in Arabidopsis thaliana

Abstract: Alternative splicing (AS) of pre-mRNAs is an important regulatory mechanism shaping the transcriptome. In plants, only few RNA-binding proteins are known to affect AS. Here, we show that the glycine-rich RNA-binding protein AtGRP7 influences AS in Arabidopsis thaliana. Using a high-resolution RT–PCR-based AS panel, we found significant changes in the ratios of AS isoforms for 59 of 288 analyzed AS events upon ectopic AtGRP7 expression. In particular, AtGRP7 affected the choice of alternative 5′ splice sites pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 73 publications
3
128
0
Order By: Relevance
“…Studies on the impact of a small number of SFs on the transcriptome have mainly been performed under normal growth conditions with little variation in conditions (Simpson et al, 2008;Raczynska et al, 2010;Rühl et al, 2012;Streitner et al, 2012). In the future, it will be important to identify SFs and their gene targets systematically and to understand how dynamic changes in AS during stress contribute to both short-term responses and long-term adjustment or acclimation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies on the impact of a small number of SFs on the transcriptome have mainly been performed under normal growth conditions with little variation in conditions (Simpson et al, 2008;Raczynska et al, 2010;Rühl et al, 2012;Streitner et al, 2012). In the future, it will be important to identify SFs and their gene targets systematically and to understand how dynamic changes in AS during stress contribute to both short-term responses and long-term adjustment or acclimation.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of robust quantitative data on AS among ecotypes may aid the identification of key splicing regulatory elements and the position of binding sites. Quantitative differences in AS between Col and C24 using a limited number of genes/AS events revealed that 28% of the AS events showed significant changes between the two ecotypes, whereas more than 70% were not affected (Streitner et al, 2012).…”
Section: Natural Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…These two proteins are controlled by the circadian clock, and their protein levels are regulated similarly to PTBs by AS and the production of NMDsensitive transcripts (Carpenter et al, 1994;Heintzen et al, 1994;Staiger, 2001;Staiger et al, 2003). Using a high-resolution RT-PCR panel, it was shown that GRP7 affects 59 events from a total of 288 AS events tested (Streitner et al, 2012). RIP experiments confirmed binding of GRP7 to seven targets that was dependent on the RRM domain.…”
Section: Trans-acting Factorsmentioning
confidence: 97%